Metaphysics of Presence With Husserl - Farha, Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
. The western philosophy could generally be best described as, Derrida called it, the Metaphysics of Presence. It is intellectual movement that started with the Greek philosophers and reached its peak with Heigel through the concept of metaphysics. The research question here is how such an intellectual movement has specifically promoted through a specific subject matter, which is the transference from the moment of metaphysics into that of presence, in other words, the alteration of the metaphysical concept of existence, as it is per se, into concept of absolute presence. Accordingly, in this piece of research, we shall endeavor to highlight how the concept of metaphysics, with Husserl, uncovers itself through three key points, as follows: 1. Intuition is epistemological basis to authentic positivism. 2. The transcendental domain is that of existence. 3. The existence that presents itself via intuition is an epistemological moment. This means, existence itself is simultaneously both the absolute presence and the metaphysical moment. Thus, we shall prove that Husserl possesses a presuppositions which is the metaphysics of presence.